2019
DOI: 10.3389/fpsyg.2019.02532
|View full text |Cite
|
Sign up to set email alerts
|

The Thin White Line: Adaptation Suggests a Common Neural Mechanism for Judgments of Asian and Caucasian Body Size

Abstract: Visual adaptation has been proposed as a mechanism linking viewing images of thin women’s bodies with body size and shape misperception (BSSM). Non-Caucasian populations appear less susceptible to BSSM, possibly because adaptation to thin Caucasian bodies in Western media may not fully transfer to own-race bodies. Experiment 1 used a cross-adaptation paradigm to examine the transfer of body size aftereffects across races. Large aftereffects were found in the predicted directions for all conditions. The strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
(52 reference statements)
2
12
0
Order By: Relevance
“…3 ). A recent study 20 had used visual adaptation to study the after-effect following repeated exposure of Asian or Caucasian female bodies, and their results seemed to be consistent to our findings. They also reported a lack of “other-race effect” at the stimuli level, but they reported that Asian participants seemed to show a weaker adaptation effect relative to Caucasians; however, the effect was not specific to Asian or Caucasian stimuli.…”
Section: Discussionsupporting
confidence: 89%
“…3 ). A recent study 20 had used visual adaptation to study the after-effect following repeated exposure of Asian or Caucasian female bodies, and their results seemed to be consistent to our findings. They also reported a lack of “other-race effect” at the stimuli level, but they reported that Asian participants seemed to show a weaker adaptation effect relative to Caucasians; however, the effect was not specific to Asian or Caucasian stimuli.…”
Section: Discussionsupporting
confidence: 89%
“…Whether or not adaptation is relevant to cases such as these has yet to be determined, but even if it is not, this technique remains an invaluable non-invasive method of probing the brain mechanisms underlying body perception. So far, adaptation studies have revealed these mechanisms to be high level (Hummel et al, 2012b ; Brooks et al, 2018 ), and selective for identity (Brooks et al, 2016 ) and gender (Brooks et al, 2019 , 2020a ), yet they generalize across race (Gould-Fensom et al, 2019 ). There also appear to be independent neural populations responsible for the perception of fat and muscle mass (Sturman et al, 2017 ; Brooks et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…We employed a visual body size adaptation paradigm similar to our previous research (Brooks, Baldry, et al, 2019;Gould-Fensom et al, 2019) and tested the effect of body size adaptation on the visual perception of body size as well as tactile distance.…”
Section: Methodsmentioning
confidence: 99%
“…For the visual task, we measured the visual PSN we used a method of adjustment task (Brooks et al., 2019; Gould‐Fensom et al., 2019). In each visual response trial, participants moved the mouse horizontally (starting position was randomized; mouse pointer was not visible) to move through the 13 possible versions of each body (see Figure 1B).…”
Section: Methodsmentioning
confidence: 99%